First‐class universities, economic development, and the middle‐income trap - Jinxiong Chang; Yan Sun; Liuchen Zhang (International Studies of Economics)
Abstract First‐class universities play an extremely important role in cultivating high‐quality talents and technological innovation, serving as a significant indicator of a country's level of higher education development, developmental strength, and potential. However, there is little literature studying the long‐term impact of first‐class universities on a country's economic development. To better understand this long‐term influence, our study examines the effect of first‐class universities on per capita income based on cross‐national samples, particularly their role in overcoming the “middle‐income trap,” and analyzes whether general higher education can bring about equivalent effects. The main research conclusions are: First, both general higher education and first‐class universities can significantly improve a country's per capita income, but compared to general higher education, first‐class universities have greater marginal effects on national per capita income, and can more effectively enhance domestic average income levels and promote sustainable economic growth over time; Second, first‐class universities have the greatest marginal effect on improving per capita income in middle‐income countries, and compared to general higher education, first‐class universities play a larger role in helping developing countries break through the “middle‐income trap”; Third, both general higher education and first‐class universities positively affect innovative activities, but first‐class universities play a more significant role in promoting technological innovation, which can better facilitate high‐quality economic development. Our study not only enhances the understanding of the effects and differences between general higher education and first‐class universities on long‐term economic development, but also contributes to the understanding of the economic miracle that China has created since its reform and opening up. It also provides clear policy implications.